Bacteriological and Physicochemical Study of Retailed Cow Milk collected from Different Locations in Birnin Kebbi - Muhammad Muhammad, Shamsudeen; Abubakar Tomo , Farida (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2023)
Abstract Milk is an excellent source of both major and minor components needed to meet the nutritional requirements of the human body. The current study was conducted to evaluate the bacteriological and physicochemical quality of cow milk collected from various locations in Birnin Kebbi. A total of twenty-four (24) milk samples (six from each location) were purchased. All samples were subjected to bacteriological analysis using total plate count, and physicochemical composition analysis, which included PH, moisture content, fat content, protein content, and mineral determination (calcium, sodium, and potassium). The mean range for Total Plate Count is 1.83x106-3.42x106 CFU/ML. Furthermore, bacteria isolated and identified from milk samples include Streptococcus spp, Shigella spp, Escherichia coli, Bacillus spp, Staphylococcus aureus, and Proteus spp. The physicochemical analysis results indicated that the mean range is PH (4.87±0.04-5.52±0.05) Moisture content (82.22±0.60-87.50±2.16), Fat content (0.56±0.02-1.84±0.01), Protein content (11.27±4.4-12.55±4.99), Calcium (173.83±4.43-475.67±22.24), Sodium (11.83±4.26- 111±12.44) and Potassium (131±9.12-596±6.16) respectively. The study's findings highlight the poor bacteriological quality of milk, as evidenced by a higher Total Plate Count. Moreover, the presence of pathogenic microbes in milk, such as Bacillus spp, Shigella spp, and Escherichia coli, is likely to pose a serious public health risk. As a result, it is recommended that proper hygiene practices be implemented, as well as the incorporation of effective monitoring throughout the production to delivery chain.